Psicoprofilaxis Obstétrica: Actualización, definiciones y conceptos - Morales Alvarado, Sabrina; Guibovich Mesinas, Alex; Yábar Peña, Maribel (Horizonte Médico (Lima), 2014)
Obstetric Psychoprophylaxis: Update, definitions and concepts